Parental involvement in early childhood literacy: International programs & Egyptian experiences - Ibrahim, Lojain Tamer (AUC Knowledge Fountain, 2016)
Research has demonstrated the importance of the early years in children’s literacy skills development and shown how children who acquire some literacy skills before school entry are at more advantage in later conventional literacy acquisition than their peers who haven’t. Moreover, several studies have examined the role parents have in their children’s early literacy development and found the parental involvement factor to be of great significance. In response to such findings and to problems such as scarcity of data about early childhood education and parental involvement in children’s early literacy development in the MENA region and Egypt in particular, this study has been designed with the purpose of initial in-depth examination of perceptions of Egyptian parents from different socioeconomic statuses (SES) when it comes to involvement in their children’s early literacy development. The study used questionnaires as a tool that included both open-ended and close-ended questions to provide qualitative and quantitative data. Participants in the study were 22 parents of kindergartners, 12 mother from a high SES and 10 from a low SES (8 mothers and 2 fathers). The study examined five themes within both SES levels: KG standing in terms of enrollment rates and quality, parental awareness, parental willingness to participate in children’s education and literacy development, parental capabilities, and parents’ views on gender roles when it comes to involvement in children’s educational development. Data findings were thematically analyzed and showed that: 1. Egyptian parents from high and low SES enrolled/want to enroll their children in kindergartens yet parents from low SES find public facility fees as barriers; as for quality, the study showed parents from high SES were more satisfied with the private facilities their children go to than parents from low SES whose children went to public kindergartens. 2. Parents from high and low SES had high awareness and willingness to participate in their children’s early literacy development, yet parents from high SES had significantly higher capabilities than parents from low SES. 3. Parents from high and low SES faced the same reality where mothers were more involved in children’s early literacy, yet parents from high SES were more aware of the importance of both parents (mothers and fathers) participating in children’s education and literacy development.